Effect of Tunceli garlic on some immunological parameters in Cyprinus carpio exposed to chlorpyrifos - Pala, Ayşegül; Åžeker, Engin; Yonar, M. Enis (Cellular and Molecular Biology, 2018)
In this study, the effect of Tunceli garlic (Allium tuncelianium) on hemoglobin (Hb) level, oxidative radical production of neutrophils (Nitoblue tetrazolium assay-NBT activity) and total immunoglobulin (TI) content in carp (Cyprinus carpio) exposed to chlorpyrifos (CPF) was investigated. The 96 hour LC50 value of CPF on C. carpio was calculated to as 0.230 mg/L. The fishes were exposed to sublethal concentration of chlorpyrifos (1/8 of LC50 value: 0.029 mg/L), and Tunceli garlic (20 and 40 g/kg diet) was simultaneously administered for 21 days. Blood samples were taken from the fishes at 7, 14 and 21 days and analysed to determine the Hb levels, the NBT activity and the TI content. There was a significant decrease in the Hb level, the NBT activity and the TI content of CPF-treated fish. However, Tunceli garlic reversed the Hb level, the NBT activity and the TI content. In conclusion, this study demonstrated that CPF had a negative effect on the immunological values of the fish. The simultaneous administration of Tunceli garlic was neutralised CPF-induced toxicity.